Links Between Surgical Landmarks of the Temporal Bone and Cochlear Implant Approaches - Gabriel Lostun (Acta Medica Marisiensis, 2015)
Objective: We aimed to underline the surgical importance of the distances between the landmarks of the temporal bone, important for quantifying the benefits and disadvantages of two different cochlear implant techniques.